IKLIM ORGANISASI SEKOLAH MEMODERASI PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA GURU SMK NEGERI DI KABUPATEN PATI - Winarto, Winarto; Srimindarti, Ceacilia (Jurnal Ilmiah Telaah Manajemen, 2014)
This study is aimed to examine the effect of school organization climate in moderating the influence of work motivation and competence on teacher performance of state vocational school in Pati regency. The purposes of this study are to clarify and extend previous research on the effect of school organization climate in moderating the influence of work motivation and competence on the teacher's performance of state vocational school in Pati regency. The population in this study was 323 teachers. While the samples were taken by using Slovin formula by significance level α = 0.05, with a spread proportional to each school by proportional random sampling. Data was collected using questionnaires, and after that data was processed by using SPSS 19. Results of the study showed (1) motivation has positive and significant impact to the teacher’s performance, (2) competency has positive and significant impact to the teacher’s performance, (3) organization climate has positive and significant impact to the teacher’s performance, (4) organization climate moderates the influence of work motivation on teacher’s performance, (5) organization climate moderates the influence of competence on teacher’s performance. Keywords: Motivation, Competence, Organizational Climate, Performance